(untitled) - AGUNG ISNAENI, MUCHAMMAD (Jurnal Ilmu Manajemen (JIM), 2016)
This study focused on the product innovation of Fruit Coffee Cafes Refresho in Tulungagung. The purpose of this study is to analyze and determine the influence of product innovation to customer loyalty with customer satisfaction as an intervening variable in the study of consumer Fruit Coffee Refresho in Tulungagung. Population in this research is that consumers Fruit Coffee Refresho who have visited and purchased at Café Refresho at least three times with the characteristics of consumers ages ranging from 17-35 years. In this study using Path Analysis with Amos software support 20. The results showed that product innovation of Fruit Coffee Cafes Refresho in Tulungagung has a significant influence on customer satisfaction. Product innovation also positively affects to customer loyalty. Keywords:product innovation, customer satisfaction, and customer loyalty